Neuroanatomical correlates and linguistic deficit in alzheimer disease: early diagnosis (2020)
The Alzheimer disease (AD) is the most common cause of neurodegenerative insanity that leads to irreversible neuronal loose and progressive deterioration of cognitive functions. The actual criteria to diagnosis present the drawback that when they’re done an insanity has already developed, so that is late to modify the disease path through an intervention. Because of that, this paperwork has given the job to review studies about the correlations made in early affected brain areas (hippocampus, entorhinal cortex, and neocortex), and those neuropsychological trials that detect cognitive changes, especially linguistic, in prodromal AD. The used methodology consist in the bibliographic research of the last 15 years.